Enhancing Oxygen Reduction Reaction Activity Using Single Atom Catalyst Supported on Tantalum Pentoxide. Issue 11 (12th April 2022) - Back, Seoin; Bagherzadeh Mostaghimi, Amir Hassan; Siahrostami, Samira
Abstract: Transition metal oxides have emerged as promising cost‐effective alternatives to Pt catalysts for oxygen reduction reaction (ORR) in fuel cell applications. However, their low stability under harsh electrochemical conditions hinders their widespread applications. Tantalum pentoxide (Ta2 O5 ) has proven to be a stable material under ORR conditions, but its activity is limited. In this work, we incorporate single atom catalysts (SACs) in Ta2 O5 to resolve the limited ORR activity of this material by altering the electronic structures of surface Ta atoms. We use density functional theory (DFT) calculations to identify the most promising SACs with enhanced ORR activity. Pt, Rh, and Ir, are found to be the most promising SACs with improved ORR activity and high stability. This work suggests that SACs are effective in enhancing Ta2 O5 catalytic activities for ORR. Abstract : All the single atoms : Single atom transition metal doped into Ta2 O5 are found to be promising for oxygen reduction reaction.